The Relationship Between Inflation and Interest Rates: Evidence from Emerging Economies - Bakoeva Gulbakhor (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This paper examines the dynamic relationship between inflation and interest rates across emerging economies. It investigates whether the Fisher Effect, which suggests that nominal interest rates move one-for-one with expected inflation, holds true in these markets. Using empirical data from selected emerging economies between 2010 and 2023, the study employs panel cointegration and causality analyses to evaluate both short-term and long-term linkages. The results indicate that while the Fisher relationship is partially valid, monetary policy regimes and inflation expectations significantly influence deviations from it.